ICT (Instruction Computer Technology) Based PKN and IPS Learning Designs in Elementary Schools - miranda; Yeni Erita; Rena ELIA (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
The learning process that is usually carried out in schools or what is often referred to as the conventional learning system is now seen as less effective. In the current era of globalization, ICT (Information and Communication Technology) is a requirement that is used as the basis for determining the quality and effectiveness of the learning process. Designing ICT-based IPS-Civics learning can help teachers or students in the learning process so that knowledge and learning materials can be conveyed to students properly. This research was obtained and collected through literature studies, which were carried out by literature review and from searches carried out on the internet via Google. ICT-based learning media, namely learning media in which all electronic components consist of hardware and software as well as all activities related to data processing, retrieval, collection (acquisition), processing, storage, dissemination, and presentation of information/data using computers and telecommunications. ICT-based learning media include: computer technology, multimedia, telecommunication, and computer network technology. The function of ICT in learning media is as a tool in learning media, learning facilities/places, as a source of learning, and as a means of increasing professionalism. The purpose of this research is to make it easier for teachers to develop learning designs that use information technology so that learning becomes less monotonous and more creative, especially in Social Studies and Internship learning which is often considered boring by students, using ICT-based learning designs will attract more students' attention keywords: Learning Design, Civics, and Social Studies, ICT (Instruction Computer Technology).